A Retrospective Review of Lead Migration Rate in Patients Permanently Implanted with Percutaneous Leads and a 10 kHz SCS Device. (4th February 2021) - Gupta, Mayank; Abd-Elsayed, Alaa; Hughes, Meghan; Rotte, Anand
Abstract : Background . Spinal cord stimulation (SCS) has been used over decades for pain management, but migration of percutaneous leads has been the most common complication. Better surgical techniques and newer SCS technologies likely reduced the incidence of lead migration requiring surgical revision, although data are sparse. This study aimed to retrospectively evaluate the incidence of clinically significant percutaneous lead migration in patients permanently implanted with a 10 kHz SCS system. Methods . Consecutive patients with chronic trunk and/or limb pain, permanently implanted between January 2016 and June 2019, were included in the analysis. Data were collected from the hospital's electronic medical records and the manufacturer's database. Clinically significant lead migration, defined as diminished pain relief followed by surgery to correct lead location, was assessed at the 6-month follow-up. Results . At the 6-month follow-up, there were no cases of clinically significant lead migration, average pain relief was 65.2%, 82% of patients had response (≥50% pain relief), improvement of function was noted in 72% of patients, and decrease of medication was observed in 42% of patients. Therapy efficacy was sustained in patients with >12 months follow-up; the average pain relief was 58.5%, and the response rate was 82%. Conclusions . The surgical techniques in use today are designed to minimise the risk of percutaneous lead migration and may have reduced its incidence. In addition, new SCS systems may give greater opportunity to mitigate cases of minor lead movement using alternative stimulation programs.